(untitled) (Bangladesh Journal of Botany, 2018)
Keeping in view the dearth of well-defined saffron germplasm, an exploration trip was conducted to collect saffron germplasm from the growing tracts of Kashmir valley. A total of 28 diverse accessions were collected and evaluated. Data recorded was subjected to basic statistical analysis viz., minimum, maximum, mean and coefficient of variance as well as Shannon-Weaver Diversity Index (SDI) was also worked out. Correlation study was done to know the extent and pattern of contribution among the traits and saffron yield. An attempt was made to quantify the extent of diversity present among the accessions explored and evaluated with the help of NTSYSpc software; dissimilarity coefficient and a dendogram was drawn. Presence of good variability in respect of vegetative, agro-morphological traits as well as reproductive traits like days to anthesis (35 - 44 days), duration of flowering (15 - 21 day), No. of flowers per plant (2 - 4), style length (26 - 32 mm) and saffron (style) weight, confirmed that there is tremendous scope of improvement in saffron production. The Shannon-Weaver Diversity Index (SDI) ranged from 0.08 to 0.25. Style length and dry saffron weight showed good amount of diversity as compared to the other parameter. Correlation study confirmed that corm size is a single trait which influences vegetative growth (plant height and number of leaves) positively. This genetic stock tagged with known potential could be utilized for current need as well as for future hybridization programme with its close relatives viz., C. thomasii and C. cartwrightianus.